Implementasi Model Pembelajaran Kooperatif Tipe Jigsaw untuk Meningkatkan Aktivitas dan Hasil Belajar IPA Kelas V SD: Implementation of Jigsaw Type Cooperative Learning Model to Increase Activities and Science Learning Outcomes of Class V SD - Era Mustika Sari; Afreni Hamidah; Hadyanto Hadyanto (Edu-Sains: Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2021)
Based on the unsatisfactory student learning outcomes, so it is necessary to apply a learning method to improve student learning outcomes, the researcher is interested in applying the JIGSAW model. This research is a classroom action research involving 40 students of class V at SDN 84/IV Jambi City. This study uses the research design of Kemmis and Mc. Taggart which consists of three cycles. In each implementation cycle there are three meetings and each cycle consists of four stages, namely planning, implementing, observing, and reflecting. It is recorded on the initial score of the class average value of 33 with a proportion of 0%. So the research results obtained in the action cycle 1 class average value reached 59 with a total learning completeness of 11 students or 28%. In the action cycle II, the class average value was 69.25 with the total learning completeness of 22 students or 55% and in the action cycle III, the class average value reached 80 with a total learning completeness of 100%. This means that learning in cycle III has fulfilled indicators of success based on the class average value of 80%, so it can be concluded that improving learning using the JIGSAW type cooperative learning model can improve student learning outcomes in class V SDN 84/IV Jambi City.